Aduhelm, a novel anti-amyloid monoclonal antibody, for the treatment of Alzheimer’s Disease: A comprehensive review - Hannah W. Haddad; Garett W. Malone; Nicholas J. Comardelle; Arielle E. Degueure; Salomon Poliwoda; Rachel J. Kaye; Kevin S. Murnane; Adam M Kaye; Alan D. Kaye (Health Psychology Research)
Alzheimer's disease (AD) is the most common form of dementia affecting millions of individuals, including family members who often take on the role of caregivers. This debilitating disease reportedly consumes 8% of the total United States healthcare expenditure, with medical and nursing outlays accounting for an estimated \$290 billion. Cholinesterase inhibitors and N-methyl-D-aspartate receptor antagonists have historically been the most widely used pharmacologic therapies for patients with AD; however, these drugs are not curative. The present investigation describes the epidemiology, pathophysiology, risk factors, presentation, and current treatment of AD followed by the role of the novel monoclonal antibody, Adulhelm, in the treatment of AD. Currently, Adulhelm is the only Food and Drug Administration (FDA) approved drug that acts to slow the progression of this disease. Adulhelm is an anti-amyloid drug that functions by selectively binding amyloid aggregates in both the oligomeric and fibrillar states. Studies show Adulhelm may help to restore neurological function in patients with AD by reducing beta-amyloid plaques and reestablishing neuronal calcium permeability. At present, there is concern the magnitude of this drug's benefit may only be statistically significant, although not clinically significant. Despite skepticism, Adulhelm has proven to significantly decrease amyloid in all cortical brain regions examined. With such high stakes and potential, further research into Adulhelm's clinical efficacy is warranted in the treatment of AD.